'If I Had a Family, There Is No Way That I Could Afford to Work Here': Juggling Paid and Unpaid Care Work in Social Services. Issue 6 (November 2015) - Charlesworth, Sara; Baines, Donna; Cunningham, Ian
<x xml:space="preserve">Abstract</x> Drawing on three case studies in each of Australia, New Zealand and Scotland, this article explores how care workers employed in the social services sector negotiate their unpaid care responsibilities in the context of lean work organization and low pay. For younger workers, the unrelenting demands of service provision and low pay made any long‐term commitment to working in social services unrealistic, while many female workers experienced significant stress as they bent their unpaid care responsibilities to the demands of their paid work. However, male workers, less likely to have primary caring responsibilities, appeared less troubled by the prioritizing of paid over unpaid care work and less likely to self‐exploit for the job. At the same time, there is a widespread acceptance across different national and organizational contexts that the work/family juggle is a personal responsibility rather than a structural problem caused by the demands of underfunded and overstretched organizations.